Avulsion of Permanent Mandibular Incisors: A Report of Two Cases with Pertinent Literature - Ibadat Preet Kaur; Jitendra Sharan; Pallawi Sinha; Ashok Kumar; Anand Marya (Case Reports in Dentistry)
Introduction. This study reports two rare cases of avulsion of permanent mandibular incisors with their sequelae after being reimplanted by two contrary methods. The relevant literature regarding the avulsion of permanent mandibular incisors is also being discussed. Case Presentation. In Case I, a 9-year-old girl reported an avulsion of the permanent mandibular left lateral incisor that was immediately reimplanted within 20 minutes after injury, whereas in Case II, all four permanent mandibular incisors were avulsed and reimplanted after a prolonged extraoral dry time of 36 hours in an 18-year-old female. Both cases missed their scheduled follow-up visits and were reported after 3.5 years and 7 months, respectively, with severe root and alveolar bone resorption that was confirmed by clinical examination and Intra oral periapical radiograph (IOPA) radiographs. Discussion. Avulsion of permanent mandibular incisors is rare. The similar unfavorable outcome of contrary cases at a variable duration of time after missed follow-up illustrates the role of the appropriate treatment protocol and regular follow-up visits for the long-term success of reimplanted teeth.